Risk factors for acute otitis media in primary school children: a case-control study in Central Java, Indonesia - Siwi Pramatama Wijayanti; Daniel Joko Wahyono; Dwi Sarwani Sri Rejeki; Devi Octaviana; Aris Mumpuni; Anton Budhi Darmawan; Wahyu Dwi Kusdaryanto; Gita Nawangtantri; Dodi Safari (SAGE Publishing, 2021)
Background: Acute otitis media (AOM) is the most common disease in young children requiring antibiotic treatment. Information on AOM-related determinant risk factors in primary school children is still limited, particularly in Indonesia. This study aims to identify risk factors related to AOM in primary school children in Banyumas Regency, Central Java, Indonesia. Design and Methods: This is an analytical study with a case-control design in Banyumas Regency, Indonesia. 3574 children from 6 regions of the Banyumas Regency were recruited for the screening of AOM detection, and confirmation of AOM diagnosis was determined by Otolaryngologist. One hundred and twenty-five cases and 125 control were involved in this study. Data collection was carried out using a structured questionnaire focusing on several variables such as household cooking fuel, house environment, smoking exposure, knowledge of parents, and nutrition status. Univariate, bivariate using chi-square and multivariate with regression logistic was conducted for data analysis.  Results: This study highlights the risk of household firewood use (p=0.003), poor nutritional status (p=0.009), and a family history of ear infections (p=0.015) with an increased risk of otitis media. Conclusions: Household firewood use, poor nutritional status and family history of ear infection are factors associated with the occurrence of acute otitis media. It is necessary to provide public health education to prevent exposure to fuel at risk for children and to improve their nutritional status.